Thermal Comfort in Two Housing Typologies in the Andean Region of Ecuador: Cotopaxi Province - Rojas, María Augusta (2023)
In Ecuador, rural housing in the Andean region has limitations in its implementation and construction, which lacks technical criteria. This is due to scarce research considering the geographical and climatic conditions and the characteristics of construction materials suitable for this type of housing. This study analyzes the thermal comfort of two cases of study located in the Province of Cotopaxi, Ecuador. This location's altitude exceeds 2,900 MASL, and the average temperature ranges between 12°C and -3°C. The selected samples are two predominant single-family housing typologies in the region: the first, with a traditional construction system and the second, with a conventional system. This study has three main parts: in-situ data collection with measurement equipment, user interviews, and software simulations to obtain thermal data. The first phase, data collection and interviews, facilitate the analysis of discomfort hours and operating temperature (OT) of the current state of the housing. These first results allowed the second phase of this study, which is simulation. In this part, modifications of materiality and carpentry were proposed. The results show significant improvements in thermal comfort. Housing 1 increases by 14% of OT, and Housing 2 increases by 23% of O. T. Both study cases show a significant reduction in the discomfort hours. This research's main conclusion is that adequate material management through software simulation can contribute to innovative solutions for thermal comfort. The outgoing results of this study can be used in future housing and interventions in the region.